Analytical Model of Crack Width in Hogging Moment Regions of Steel–Concrete Composite Beams Under Fatigue Loading - Song, Aiming; Xu, Hongtao; Wan, Shui; Luo, Qi (Frontiers in Materials, 2022)
A modified formula for average crack spacing and a numerical model for crack width in hogging moment regions of steel-concrete composite beams under fatigue loading are proposed in this paper. Firstly, the existing calculation formulas and test data of average crack spacing are discussed and summarized. Through introducing the factor of transverse reinforcement spacing, a modified formula of crack spacing is suggested based on the method of nonlinear fitting. Then, a numerical model is proposed for crack width in negative moment regions under fatigue loading. In the analytical model, the explicit formulations of slip occurring at both the beam-slab interface and the reinforcement-concrete interface are included by considering fatigue effect, as well as the stress of reinforcement in the cracked section. Finally, a fatigue test on two steel-concrete composite plate beams subjected to hogging moment is designed and conducted. Compared with the crack width evaluation methods in existing literature, the analysis results of the numerical model show more reasonable agreement with the data of the experimental beams performed in this study.